Wild Rodent Ectoparasites Collected from Northwestern Iran - Zarei, Zabihollah (J Arthropod Borne Dis, 2017)
BACKGROUND: Rodents play an important role as reservoir of some pathogens, and the host of some ectoparasites as well. These ectoparasites can transmit rodents’ pathogens to human or animals. The aim of this study was to assess the distribution and infestation load of ectoparasites on rodents in Meshkin-Shahr District, northwestern Iran. METHODS: Rodents were captured using baited live traps in spring 2014 from Meshkin-Shahr District and were transferred to the laboratory for identification to the species level. Their ectoparasites were collected, mounted and identified. RESULTS: Three rodent species including Meriones persicus (74%), Mus musculus (16.9%) and Cricetulus migratorius (9%) were identified. Among all rodents, 185 specimens (90.69%) were infested with a total of 521 ectoparasites. Overall, 10 arthropods species were collected, including fleas (97.6%), one mite (1.6%) and one louse species (0.6%) as follows: Xenopsylla nubica, X. astia, X. buxtoni, X. cheopis, Nosopsyllus fasciatus, N. iranus, Ctenocephalides felis, Ctenophthalmus rettigismiti, Ornithonyssus sp and one species of genus Polyplax. The most prevalent ectoparasites species was X. nubica (89%). CONCLUSION: Nearly all rodent species were infested with Xenopsylla species. Monitoring of ectoparasites on infested rodents is very important for awareness and early warning towards control of arthropod-borne diseases.